Multi-stakeholder policy modeling for collection and recycling of spent portable battery waste. Issue 7 (July 2018) - Gupta, Vimal Kumar; Kaushal, Rajendra Kumar; Shukla, Sheo Prasad
Policies have been structured for collection and recycling of spent portable battery waste within a framework of stakeholders (recycling council body, producer, recycler and consumer) especially for those battery units that are discarded worldwide because of their expensive cost of recycling. Applicability of stakeholders' policies in their coalition framework have been reviewed and critically analyzed using the Shapley value of cooperative game theory models. Coalition models for 'manufacturer and recycler' indicated the dominating role of manufacturers over the recyclers, and waste management is highly influenced by producer responsibility. But, the take-back policy enables recyclers' dominance role in the management and yields maximum benefit to both recyclers and consumers. The polluter pays principle has been implemented in formulating policies to key stakeholders, 'manufacturers' as well as 'consumers', of battery products by the introduction of penalties to encourage their willingness to join the Environment, Health and Safety program. Results indicated that the policies of the framework have the potential to be implemented within a marginal rise in battery price by 12% to 14.3% in the range of recycling cost per tonne of US2000 to US5000. The policy of the stakeholders' framework presented in the study could be an important aid to achieve high collection and recycling rates of spent portable batteries.